Геолого-демографічна модель процесу народонаселення Землі. Стаття I - Хтема, А.В.; Хтема, В.М. (Геоінформатика, 2016)
За допомогою трактування космофізичної моделі процесу еволюційного розвитку Землі спільно з демографічними даними і використанням механізму зворотного зв’язку створено геолого-демографічну модель із максимально можливою прогнозною компонентою та отримано значення параметрів процесу народонаселення за різних сценаріїв і варіантів його розвитку. Оцінено загальну тривалість процесу народонаселення – від появи перших і до зникнення останніх людей, як істот, критично залежних від матеріально-енергетичної структури планети. С помощью толкования космофизической модели процесса эволюционного развития Земли совместно с демографическими данными и использованием механизма обратной связи создана геолого-демографическая модель с максимально возможной прогнозной компонентой. Получены значения параметров процесса народонаселения при различных сценариях и вариантах его развития. Дана оценка общей длительности процесса народонаселения – от появления первых и до исчезновения последних людей как существ, критически зависимых от материально-энергетической структуры планеты. The purpose of the paper is to develop a geological-demographic model of the Earth’s human population process with a long-term forecasting element; to get a digital and graphic format of the information on a probable value of parameters of human population process in various scenarios and variants of its development.
Design/methodology/approach. Comparison of cosmophysical model of Earth’s evolutionary development with demographic model of hyperbolic population growth. Comparison of the scheme of first human beings appearance with a typical scheme of branching chain reaction. We used the anthropic principle and feedback mechanism, statistic methods of demographic data processing, and empirical relationship and space-stratigraphic ranking of the earth-type planets.
Findings. As a result, we have created a geological-demographic model, and made a forecast of continuance of the human population process. This process starts from the time of first human beings appearance till the time of last human beings disappearance. The last human beings are considered to be creatures critically dependent on the planet’s energy condition.
Practical value/implications. The study permitted to obtain so for unobserved and not measured geological-demographic and astronomical data. These data allows us to extend theoretical and practical possibilities of geoinformatics, demography, and astrobiology. As a result, it will make possible to upgrade validity of long-time demographic and cosmologic predictions. Further directions for geological-demographic research should preferably be associated with spatially-temporal localization of areas with the minimum intensity and capacity of future physical-geological and climatic processes.